The relationship between service quality and customer satisfaction at Hospital Sultanah Bahiyah at Kedah / Haizatul Nadia Rosli - Rosli, Haizatul Nadia (2014)
The relationship between service quality and customer satisfaction has received considerable academic attention in the past few year. This research was aimed at examining the relationship between service quality and customer satisfaction with the data obtained from Hospital Sultanah Bahiyah at Kedah. The result of which would enable the hospital to improved the quality of services. This researcher conducted by using correlation research. Correlation research is a method used to provide some indication as how two or more things are related to one another or, in effect, what they share or have in command, or how well a specific outcome might be predicated by one or more pieces of information (Salkind,2012). In research methodology , content the research design, sampling frame, population, sampling technique, sampling size, unit of analysis, data collection procedures, instrument, validity of instrument and plan for analysis. The outcomes of the variable showed reflected a high correlation with customer satisfaction. With respect, the finding of this study can be used as a guideline by the Hospital Sultanah Bahiyah to improve the quality of services. For security reasons, certain information affecting customer satisfaction could not be examined in details. The result indicate that good relationship exists between service quality dimensions (core service, human element of service and tangible of services) and customer satisfaction. This research present key result on services quality and customer satisfaction research by looking at the niche segment which was not previously studied from the Malaysia perspective.